The curious case of Wang Yuandongyi: why do some want to fight with anti-ISIS groups? - Jayakumar, Shashi (2016)
The arrest in March 2016 of a Singapore citizen, Wang Yuandongyi, for attempting to travel to Syria to fight with a Kurdish militia against ISIS raises questions about the psychological processes of individuals attempting to join anti-ISIS groups.Should these individuals be treated in the same manner as those attempting to fight for ISIS?